The Impact of Social Media Communication on Youth Identity Formation: A Cross-Cultural Analysis - Nugraha, Aat Ruchiat; Sjoraida, Diah Fatma; Rembe, Elismayanti; Guna, Bucky Wibawa Karya; Sani, Asrul; Suhardi, Suhardi; Fitria, Arie (eScience Humanity Journal, 2024)
This study aims to analyze the impact of social media communication on the formation of adolescent identity from a cross-cultural perspective. Using cross-cultural analysis methods, this study investigates how adolescents from different countries and cultures interact with social media and how those interactions affect the formation of their identities. The results of the study show that social media plays an important role as an important space for adolescents to uncover, express, and negotiate their cultural identity. Social media platforms provide access to a wide range of cultural expressions, allowing for the blending and transformation of traditional and modern cultural elements. However, research also shows that the influence of social media can lead to cultural homogenization and the potential loss of unique local cultural identities. In addition, the study also found that social media use can influence teens by offering a sense of community and membership, as well as facilitating connections with like-minded friends globally.